A Year in Review on Tuberculosis and Non-tuberculous Mycobacteria Disease: A 2025 Update for Clinicians and Scientists - Christoph Lange; Graham Bothamley; Gunar Günther; Lorenzo Guglielmetti; Irina Kontsevaya; Liga Kuksa; Berit Lange; Natalie Lorent; Francesca Saluzzo; Martina Sester; Marc Tebruegge; Simone Tunesi; et al. (Pathogens and Immunity)
Background: In the field of tuberculosis and non-tuberculous mycobacterial (NTM) disease we are looking back on an exciting year 2024 with more than 10,000 publications listed in PubMed.